Performance Analysis of Castable FDM Filaments for Rapid Casting Applications - Rosley, Luqman Nur Hakim (IRC, 2018)

(untitled)
With how technology progresses every day, it seems like there are more efficient ways discovered to simplify or lower down the cost of manufacturing. In this particular study, a method of producing patterns for investment casting by means of rapid prototyping will be taken an in-depth look. This method of producing patterns will greatly serve to those who are producing an item with investment casting but at a low volume production. The traditional method which utilizes tools and dies to create the patters are great, but they cost a lot and are not feasible, financially for low volume production. To substitute the patterns development with one that is 3D printed, it requires certain parameters to be look into to ensure that the parts are within the user set standards while maintaining low cost. Three types of filaments are tested, which are standard Poly Lactic Acid (PLA), Polycast, and Moldlay. Each filament has different characteristic unique to its own. Parameters such as Thermal Expansion, Degradation Temperature plays a huge role when trying to implement such process. The workability of the filaments is also tested to ensure that the parts are aesthetically pleasing as well.